Antibacterial and Antibiofilm Activity Related to the Mechanism of Work of the Active Fraction of Moringa Leaves (Guilandina Moringa L.) to Staphylococcus Aureus - Armayanti Rindiarko Hasbrianti; Opstaria; Wiwin Herdwiani (PT FORMOSA CENDEKIA GLOBAL, 2024)
Biofilm-associated S. aureus bacterial infections are difficult to treat because bacterial cells encased in biofilms can be highly resistant to antibiotics and the immune response of the host. Moringa leaf extract contains active compounds of tannins, saponins, alkaloids, and phenols that have activity as antibacterial and antibiofilm. This study aims to determine the antibacterial activity and of extracts, mechanism of action of the most active fraction of moringa leaf ethanol extract against S. aureus.Extraction of Moringa leaves using maceration method with 96% ethanol solvent, fractionated using n-hexane, ethyl acetate, and water solvents. Antibacterial test using disc diffusion method, followed by dilution test. Observations were made using SEM and AAS. Data from the diffusion test, inhibition of biofilm formation, and biofilm degradation were analyzed using One Way ANOVA. Based on the results of the study, the ethyl acetate fraction is the most active fraction in inhibiting the growth of S. aureus in the diffusion test with an inhibition zone diameter of 15,7 mm at a concentration of 100 mg/mL and a minimum kill concentration value of 25 mg/mL. The water fraction was the most active fraction in inhibiting the formation and degradation of biofilm against S. aureus with an IC50 value of 4,049 ± 0,063 mg/mL and an EC50 value of 4,246 ± 0,050 mg/mL